2002
DOI: 10.1038/416159a
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Asian desertification by 22 Myr ago inferred from loess deposits in China

Abstract: The initial desertification in the Asian interior is thought to be one of the most prominent climate changes in the Northern Hemisphere during the Cenozoic era. But the dating of this transition is uncertain, partly because desert sediments are usually scattered, discontinuous and difficult to date. Here we report nearly continuous aeolian deposits covering the interval from 22 to 6.2 million years ago, on the basis of palaeomagnetic measurements and fossil evidence. A total of 231 visually definable aeolian l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
1,095
4
18

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,606 publications
(1,154 citation statements)
references
References 22 publications
37
1,095
4
18
Order By: Relevance
“…Other lines of geological evidence lead to similar inferences (Harrison et al, 1992). Thus, the timing of the origin of several stem lineages within Lilium appears to correspond to the final, rapid phase of Q-T Plateau uplift (Liu et al, 2006;Zhang et al, 2000;Guo et al, 2002). High rates of biological diversification occurring 8-7 Mya and attributable to Q-T Plateau uplift have also been detected in other eastern Asian organisms from Compositae to catfish (e.g., Liu et al, 2006;Zhang and Fritsch, 2010;Peng et al, 2006;Wang et al, 2005).…”
Section: H-d Mountains and Its Correlation With Rapid Diversificationmentioning
confidence: 66%
See 2 more Smart Citations
“…Other lines of geological evidence lead to similar inferences (Harrison et al, 1992). Thus, the timing of the origin of several stem lineages within Lilium appears to correspond to the final, rapid phase of Q-T Plateau uplift (Liu et al, 2006;Zhang et al, 2000;Guo et al, 2002). High rates of biological diversification occurring 8-7 Mya and attributable to Q-T Plateau uplift have also been detected in other eastern Asian organisms from Compositae to catfish (e.g., Liu et al, 2006;Zhang and Fritsch, 2010;Peng et al, 2006;Wang et al, 2005).…”
Section: H-d Mountains and Its Correlation With Rapid Diversificationmentioning
confidence: 66%
“…Though the eastern margin of the Q-T Plateau may have undergone continuous uplift beginning 20 Mya and lasting until approximately 7 Mya, it is widely accepted that phases of more rapid uplift have occurred (e.g., Harrison et al, 1992;An et al, 2001;Tapponnier et al, 2001;Song et al, 2001). For example, rapid uplift may have occurred approximately 8-7 Mya and is evident from sedimentary layers indicative of increased aridification (i.e., loess) that accumulated within the rainshadow of the plateau during that time (Guo et al, 2002). Other lines of geological evidence lead to similar inferences (Harrison et al, 1992).…”
Section: H-d Mountains and Its Correlation With Rapid Diversificationmentioning
confidence: 99%
See 1 more Smart Citation
“…2001; Guo et al. 2002), showed that the CLP experienced dramatic cooling and drying (greater seasonality of precipitation) trends during the 4–2.6 Ma (Bai et al. 2009).…”
Section: Discussionmentioning
confidence: 99%
“…615 mm, of which half falls during the summer monsoon from July to September (Ding and Yang, 2000); the central and northern parts are progressively cooler and drier. Aeolian deposition began~22 Ma in the Qin'an area, in the western part of the Loess Plateau (Guo et al, 2002a;Hao and Guo, 2007). Subsequent deposition of both aeolian red clay and loess has been on a massive scale, with up to 130 m of red clay prior to 2.6 Ma followed by up to 300 m of loess after 2.6 Ma near Lanzhou (Li et al, 1997(Li et al, , 1999, 175 m at Lingtai (Ding and Yang, 2000;Ding et al, 2002), 159 m at Baoji (Rutter et al, 1991;Liu and Ding, 1998), 135 m at Luochuan (Liu, 1985;Sun and Liu, 2000) and ca.…”
Section: The Chinese Loess Plateau and The Loess-palaeosol Sequencementioning
confidence: 99%